OPERATION ACCURACY OF ADAPTIVE FRICTION CLUTCH WITH SEPARATE FORCE CLOSURE - Mikhail Pavlovich Shishkarev; Anton Yuryevich Uglenko (Advanced Engineering Research)
The possibilit y to increase feedback gain and operation accuracy of the adaptive friction clutch is r e vealed at the expense of the friction couple separate force closure of the basic and supplementary friction groups . The load cha racteristic of the clutch is presented i n the form of a curve monotonically i n creasing in the full range of the friction coefficient variation. The obtained results of three options of the coupling fluent param e ters variability have shown that to attain a maximum operation accuracy of the clutch with separate force closure executed according to the second option, it is necessary to take the maximum possible number of friction couples of the basic friction group, and the maximum gain le v el